2020
DOI: 10.1159/000509268
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells: A Potential Therapeutic Strategy for Neurodegenerative Diseases

Abstract: Neurodegenerative disease is a kind of chronic, progressive nervous system disease characterized by neuron degeneration or apoptosis. Current treatments cannot prevent the development of the disease. Possible alternative treatments include cell therapy, especially with the use of mesenchymal stem cells (MSCs). MSCs are pluripotent stem cells with capacities for self-renewal and multidirectional differentiation. MSCs may serve as a reliable source of neural cells for potential cell replacement therapy or regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 57 publications
0
41
0
1
Order By: Relevance
“…However, recent studies showed that cell therapies using mesenchymal stem cells represent an emerging strategy for neurological lesions and disorders [ 19 , 20 ]. In addition, it has been shown that MSCs may improve the neurological disease in the following possible ways: homing to the injured site, paracrine factors, and immunomodulation [ 21 ]. Numerous studies have demonstrated the paracrine activity of MSCs via the secretion of a wide range of neurotrophic and growth factors (VEGF, BDNF, NGF, GDNF, CNTF), which are able to promote axonal growth and remyelination [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that cell therapies using mesenchymal stem cells represent an emerging strategy for neurological lesions and disorders [ 19 , 20 ]. In addition, it has been shown that MSCs may improve the neurological disease in the following possible ways: homing to the injured site, paracrine factors, and immunomodulation [ 21 ]. Numerous studies have demonstrated the paracrine activity of MSCs via the secretion of a wide range of neurotrophic and growth factors (VEGF, BDNF, NGF, GDNF, CNTF), which are able to promote axonal growth and remyelination [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mazzini et al clinical investigations deliver proof of the theory that hNSCs therapy could be effective for treating a human with ALS in the absence of any serious unwanted events (Mazzini et al., 2019). Moreover, although various in vitro and in vivo experimentations in animal models have established the therapeutic capacity of MSCs, the clinical consequences have not been inspiring (Yao et al., 2020). For instance, Mohammadi et al have reported that learning and memory abilities of AD mice models were not improved upon intrahippocampal transplantation of chorion‐derived mesenchymal stem cells (C‐MSCs), and suggested that efficacy and function of transplanted cells were not clinically satisfied (Mohammadi et al., 2019).…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Furthermore, finding a cure for neurodegenerative disease such as Alzheimer's has been a real challenge because they are not only difficult to diagnose, but drug delivery to the brain is also an intricate process. MSCs-based therapy can reinforce nerve growth by reconstructing the neural microenvironment and reducing the factors involved in damaging the nerve structure, thereby providing a treatment [ 109 ]. Another application of MSCs-based therapy has been observed for frailty, although it is known that certain diets can improve the symptoms of frailty.…”
Section: Anti-ros Therapeuticsmentioning
confidence: 99%